Use of corn-steep liquor as an alternative carbon source for biomineralization in cement-based materials and its impact on performance. (20th March 2018) - Amiri, Ali; Bundur, Zeynep Başaran
Highlights: In-vitro microbial induced calcium carbonate precipitation was evaluated. Two different nutrient media, Urea-Yeast Extract and Urea CSL were compared. Use of CSL instead of yeast extract improved the problems related to initial set. Performance of so called self-mortar was improved by using microorganisms. Abstract: Early age microcracks are generally the primary cause for a decrease in service life of cement-based structures. Recent studies suggested that it might be possible to develop a smart cement-based material that could self-heal microcracks. The use of microbial induced calcium carbonate precipitation (MICP) in cement-based materials is a novel approach to trigger self-healing and it has become an interesting field of research. MICP is a biochemical process where calcium carbonate (CaCO3 ) precipitation is obtained via metabolic pathways for microorganism and MICP via urea hydrolysis is the most common approach used in cement-based materials. Through the literature the most commonly used nutrient media for urea hydrolysis was composed of yeast extract and urea. However, use of yeast extract as a carbon source not only resulted with a severe retardation of initial setting and it increases the cost of the application. This study investigates the suitability of corn steep liquor (CSL) as an alternative replacement of yeast extract. CSL was found to be a suitable alternative for MICP applications without compromising bacterial growth, ability to promote CaCO3 precipitation. In addition, use of a nutrient medium including CSL and urea did not have such an adverse effect on initial set and compressive strength as compared to a urea and yeast extract medium.